Unveiling the obstacles encountered by women doctors in the Pakistani healthcare system: A qualitative investigation. - Ali Raza; Junaimah Jauhar; Noor Fareen Abdul Rahim; Ubedullah Memon; Sheema Matloob (PLoS ONE)
In Pakistan, women outnumber men in medical colleges with 80 percent enrollment, yet many fail to practice medicine following graduation. Pakistan Medical Council (PMC) states 50 percent of graduated women doctors either did not practice or left employment in a short period. Thus, the non-servicing women doctors are assumed as the one of the major causes for the overall doctors' shortage in the country. Addressing this enduring matter, this study aims to explore and understand the factors that discourage women doctors from practicing medicine in Pakistani hospitals. The study employed qualitative exploratory inquiry with an interpretive paradigm to attain a deeper understanding of the problem. 59-semi structured interviews were conducted by non-working women doctors across the entirety of Pakistan. The narratives were then analyzed by thematic analysis using ATLAS.ti 22. The findings have resulted in the three major themes, i.e., workplace challenges, socio-cultural obstructions, and familial restrictions that possibly obstruct women from practicing medicine in hospitals. The findings suggested that accepting traditional cultural values, including entrenched gender roles in society, deters women from practicing medicine. The prevailing patriarchal societal system includes stereotypes against working women; early marriages hinder women from practicing medicine. The prevailing societal system upholds the influence of in-laws and a husband for women doctor professional employment. As a result, severe work-life conflict was reported where most women doctors ended up in their profession in the middle of struggling between socially rooted gender roles as homemakers and their professional careers-furthermore, the study found various workplace issues that posit an additional burden on already struggling women doctors. Issues include poor recruitment and selection process, transfer constraints, excessive workload with inadequate salary, harassment, gender discrimination, unsafe work environment, and little support from the administration highly contribute to the shortage of women doctors in Pakistan.